The Effect of Using Three Step Interview on Students Writing Achievement - Kiki Aprilia Ananda Putri (Universitas Muhammadiyah Jember, 2017)
Three Step Interview technique is kind of cooperative learning techniqueimplemented for seventh grade students at MTs Baitul Hikmah to improve thestudent’s writing skill because it is one of the most important skill in educationsuccess and one of the most complex skill to be mastered. Then, the researchaimed to find the effect of using Three Step Interview on students’ writingachievement. It investigated whether students taught by using Three StepInterview technique showed better result in writing descriptive text than students who were taught by lecturing method. This is a quasi-experimental research. The subjects of this research were 35 students of seventh grade at MTs BaitulHikmah. The researcher used two groups that is Experimental and ControlGroups were given a writing test to measure their writing achievement. The datawas collected by giving pre-test and post-test focusing on writing descriptivetext. After the data were tested and found to be homogeneous variance anddistribution of the data is normal, the hypothesis was tested using IndependentSample T-test in SPSS Version 23 which showed that the significant valuesis 0,003. The value is lower than significances level of 5% which means thatNull Hypothesis (H0) is rejected. So, Alternative Hypothesis (Ha) is accepted.Therefore, it can be concluded that there is a significant effect of using ThreeStepInterview on Students Writing Achievement at MTs Baitul Hikmah in 2017/2018 academic year.